Age, Growth, and Mortality of a Trophy Channel Catfish Population in Manitoba, Canada. (1st November 2016) - Siddons, Stephen F.; Pegg, Mark A.; Hogberg, Nick P.; Klein, Geoff M.
Abstract: The Red River of the North (Red River) is managed with a unique set of regulations aimed at conserving the age structure and size structure of a trophy Channel Catfish population. Although these regulations have been in place for >20 years, current population dynamics have not been evaluated postregulation. Our objectives were to (1) document dynamic rate functions (i.e., growth and mortality), age structure, and size structure of Channel Catfish in the lower Red River, and (2) compare current population dynamics with historical conditions in the lower Red River and other populations. We documented a maximum age of 27, and ages greater than 20 were common (7%). We estimated an annual mortality rate of 0.19, which was similar to mortality estimates for Channel Catfish in the Red River from the USA. Growth rates for individuals ages 3–10 were similar among our study, historical growth estimates, and upstream estimates. Conservative harvest regulations appear to be preserving the desired age structure and size structure of Channel Catfish in the lower Red River, and this study may provide insight into unique management possibilities for other systems. Received March 11, 2016; accepted August 1, 2016 Published online October 28, 2016